Tesla: the power for the future - Sabido, Patrícia Alves Do Nascimento (2022)
Tesla's business model has disrupted the conservative automotive sector with cutting-edge electric vehicles, solar energy systems, and energy storage products. The uncertainty of the new electric vehicle market, the new players entering the market, and speculation around the company, are incremental risk factors included in the valuation model. The company has good future prospects, as it keeps investing in new plants in new geographies and increasing production capacity in order to respond to the high demand. Through the DCF valuation model, it was estimated a target price for FY22of $561, further explored in the report.